If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 12 + 3n = 2n + 30 Reorder the terms: 12 + 5n + 3n = 2n + 30 Combine like terms: 5n + 3n = 8n 12 + 8n = 2n + 30 Reorder the terms: 12 + 8n = 30 + 2n Solving 12 + 8n = 30 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 12 + 8n + -2n = 30 + 2n + -2n Combine like terms: 8n + -2n = 6n 12 + 6n = 30 + 2n + -2n Combine like terms: 2n + -2n = 0 12 + 6n = 30 + 0 12 + 6n = 30 Add '-12' to each side of the equation. 12 + -12 + 6n = 30 + -12 Combine like terms: 12 + -12 = 0 0 + 6n = 30 + -12 6n = 30 + -12 Combine like terms: 30 + -12 = 18 6n = 18 Divide each side by '6'. n = 3 Simplifying n = 3
| 12/2=x/15 | | D-3=(2) | | r^3+3r=5 | | 3x-12=15x+8 | | 7x+1.5x=32560 | | 27(n-1)=3(6) | | 3r+13r=-16 | | (x-8)2+(y+2)2=49 | | 27n-1=18 | | 2m-3n=2 | | M-4=(4) | | 4340+4125(215)=891215 | | 5k-14k+(10)=17 | | 4125+(215)=886,875 | | y^2+11y+118=0 | | 5+(10-1)(3)= | | 12b-11b=10 | | 4125(215)=886,875 | | 5a+2b=5 | | 5+(4-1)(3)= | | 7x+4-2x=10 | | 8x-(6x+8)=3x-41 | | 5(-2x-4)-3(4x+5)=9 | | 4x+4=2(3+2x) | | 2=-(p+4) | | 12+(10-1)(3)= | | 12+(1-1)(3)= | | 49x^2+14+1=0 | | 12+(4-1)(3)= | | (S+9)=8 | | 12+(n-1)(3)= | | 3x=-4x+42 |